Performance Analysis of Family Hope Program (PKH) and Their Role in Enhancing Community Welfare: A Case Study in Sumenep District, Madura - Parawansah, Rosa Indah; Pratikto, Heri; Syihabudhin, Syihabudhin (International Journal of Economics Development Research (IJEDR), 2025)
This study aims to analyze the performance of Family Hope Program (PKH) facilitators in Sumenep District, focusing on three sub-districts: Pragaan, Gili Genting, and Lenteng. The research evaluates facilitator performance based on three key dimensions: quality, quantity, and timeliness in task implementation. A descriptive qualitative approach with a case study method was employed. Data were collected through in-depth interviews, observations, and documentation involving PKH facilitators and Beneficiary Families (KPM). The findings reveal that overall, the facilitators performed their duties effectively. In terms of quality, they successfully established effective communication with KPM and provided assistance in accordance with technical guidelines. Regarding quantity, facilitators met targeted activities such as Family Capacity Building Meetings (P2K2) and periodic data updates. Concerning timeliness, most facilitators demonstrated discipline in submitting daily and monthly reports. However, certain technical challenges, particularly poor internet connectivity in island areas, hindered the reporting process. These results highlight the importance of improving digital infrastructure and providing continuous support for facilitators to enhance the effectiveness and efficiency of the PKH program, especially in remote regions.